Competition in Marketing: Survival Yardstick for Small and Medium Enterprises in Nigeria - Ibidunni, O.S.; Ogundele, O . J . K . (Mediterranean Journal of Social Sciences, 2013)
The study investigated how competition on firms’ life-cycle operations ensures the survival of small and medium enterprises inNigeria. Relevant models and theories were employed to evolve detailed analysis of issues relating to the variables used interms of competition in marketing and survival of juice-producing small and medium enterprises. Two hypotheses wereinvestigated through the survey of 20 prominent Ikeja based small and medium enterprises using Cluster sampling. 5-pointLikert summated rating scale was adopted, while Yard’s formula with 95% confidence level and 5% error tolerance was used.Alternative form validity of the instrument was measured at 0.63 while its reliability was measured at Cronbach’s alpha of 0.70.Pearson’s product-moment correlation was used in testing hypothesis 1 while standard multiple regressions were used to testhypothesis 2. Findings revealed that there was strong relationship between survival of juice-producing small and mediumenterprises with forms of competition on a firm’s life-cycle; while competition had positive effects on survival components forthe enterprises. It was concluded that since competition subsists in any firm’s life-cycle, strategies to support operations forsurvival must be adopted. It was recommended that operators of small and medium enterprises have to monitor and managecompetition as it affects their businesses positively and/or negatively.